Assessing the Effectiveness of the E-Court System Implementation Using the End-User Computing Satisfaction Model at Kotabaru District Court - Adithya, Muhammad; Samboteng, Lukman; Priyanto, Agus (Manunggal Halim Jaya, 2026)
This research investigates the effectiveness of the Electronic Court System (E-Court) implementation at the Kotabaru District Court in Indonesia, using the End User Computing Satisfaction (EUCS) model. The study aims to assess how well the E-Court system meets its objectives of improving judicial efficiency, transparency, and accessibility, and to identify the barriers that limit its full effectiveness. The research employs a qualitative descriptive approach, utilizing primary data collected through in-depth interviews, structured observations, and document analysis. Interviews were conducted with key stakeholders, including judges, court staff, advocates, and litigants, to gather insights into their experiences with the E-Court system. The EUCS model was used to analyze user satisfaction across five dimensions: content, format, ease of use, timeliness, and support. The findings indicate that while the E-Court system has significantly improved administrative efficiency, reduced time and costs, and enhanced public access to justice, challenges persist in areas such as ease of use, timeliness, and technical support. External factors such as poor internet infrastructure, geographic constraints, and limited digital literacy also hinder the system's full potential. The study concludes that the success of the E-Court system depends on overcoming these barriers through better technical support, improved user interfaces, and broader digital literacy programs. Recommendations are made for both local and national stakeholders to address these issues and enhance the inclusivity and accessibility of the E-Court platform.